Characterization of the nucleation precursor (H2SO4–(CH3)2NH) complex: intra-cluster interactions and atmospheric relevance. Issue 7 (13th January 2016) - Ma, Yan; Chen, Jiao; Jiang, Shuai; Liu, Yi-Rong; Huang, Teng; Miao, Shou-Kui; Wang, Chun-Yu; Huang, Wei
Abstract : Amines have been proposed to participate in the nucleation process, but the electron density analysis and the determination of a temperature dependence of the clusters are still lacking. Abstract : Amines have been proposed to participate in the nucleation process, but the electron density analysis and the determination of a temperature dependence of the clusters are still lacking. In this study, the clusters of (H2 SO4 ) m (CH3 NHCH3 ) n ( m = 1–2, n = 1–3) are studied using the basin-hopping method coupled with density functional theory (DFT). Considering the high flexibility and complexity of a hydrogen bonding environment, the temperature dependence of the conformational population and the relative population fraction of the clusters are investigated. Moreover, the electron density is analyzed to identify the different types of intra-cluster interactions. The results indicate that the ratio between acid and base is very important for the cluster formation. The main interaction type changes from hydrogen bonding to a weak attraction as the number of bases increase. When the number of dimethylamine molecules is less than or equal to that of the sulfuric acid molecules as the most abundant clusters in the atmosphere, we tentatively suggest that the cluster contains less than two dimethylamine molecules because the critical clusters contain two or fewer sulfuric acid molecules. This means that the sulfuric acid–dimethylamine system can only form three main small clusters in the real atmosphere. Thus, other substances, such as water or organic acids, may be involved to promote the growth of clusters, and they may also affect the nucleation. This work predicts the possible forms of dimethylamine with sulfuric acid when participating in nucleation in a theoretical approach, and provides a reliable reference for the research on the nucleation mechanism containing dimethylamine in the atmosphere.